Antibiotic resistance and molecular typing of Pseudomonas aeruginosa: focus on imipenem - Freitas,Ana Lúcia Peixoto de (2002)
Susceptibility tests by disk diffusion and by E-test and molecular typing by macrorestriction analysis were performed to determine the relatedness of Pseudomonas aeruginosa isolates from three distinct hospitals. The resistance profile of 124 isolates to 8 antimicrobial agents was determined in three different hospitals, in Porto Alegre, Brazil. Frequencies of susceptibility ranged from 43.9% for carbenicillin to 87.7% for ceftazidime. Cross-resistance data of imipenem-resistant isolates indicated that most (70%) were also resistant to carbenicillin, although 30% remained susceptible to ceftazidime and cefepime. In general, susceptibility profiles were not able to determine relatedness among isolates of P. aeruginosa. On the other hand, molecular typing by macrorestriction analysis demonstrated high discriminatory power and identified 66 strains among 72 isolates of P. aeruginosa. Imipenem-susceptible isolates were all different. However, identical clones of imipenem-resistant isolates were found in two of the hospitals, despite variable response to other antibiotics. No clustering of infection among the different medical centers was observed. In conclusion, clones of P. aeruginosa did not spread among the different hospitals in our city even though related isolates of imipenem-resistant P. aeruginosa were found.